If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(-14x + -34) = -8(26 + -7x) Reorder the terms: 4(-34 + -14x) = -8(26 + -7x) (-34 * 4 + -14x * 4) = -8(26 + -7x) (-136 + -56x) = -8(26 + -7x) -136 + -56x = (26 * -8 + -7x * -8) -136 + -56x = (-208 + 56x) Solving -136 + -56x = -208 + 56x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56x' to each side of the equation. -136 + -56x + -56x = -208 + 56x + -56x Combine like terms: -56x + -56x = -112x -136 + -112x = -208 + 56x + -56x Combine like terms: 56x + -56x = 0 -136 + -112x = -208 + 0 -136 + -112x = -208 Add '136' to each side of the equation. -136 + 136 + -112x = -208 + 136 Combine like terms: -136 + 136 = 0 0 + -112x = -208 + 136 -112x = -208 + 136 Combine like terms: -208 + 136 = -72 -112x = -72 Divide each side by '-112'. x = 0.6428571429 Simplifying x = 0.6428571429
| x^2+x-130=2 | | x+.07x=180 | | In(x+10)+In(x-4)=2Inx | | y-7=m(x+-2) | | 4(6v+6)+v=199 | | (3xy-by)/(2x-4) | | 13x+2y=-17 | | 3q-8q+13=6-8q-3 | | 4logy=2 | | (x+.07)+.10=31 | | 5cosx+7=5sinx | | 8+22x=23x+3 | | y=-(x+4)2-6 | | 2=x*240/18 | | 8m+5p=67 | | -7[1-4x]=13[2x-3] | | 8+22=23x+3 | | 17=37+4*5 | | x^3-12x^2+47x-60=0 | | 5=2u-15 | | 4g+(6+2g)3= | | -8+2u=-2 | | 2x+18=16-4[x+7] | | M-4=5/9p | | 5P-3=6p-8 | | 2x^2+21x-51=-x^2+3x-3 | | 24=w/5-6 | | 199t=99.5 | | 15m+4n=88 | | 6x-3+21=6x-3-4-8x | | p^2-5p+8=0 | | 4y+19=10y-5 |